STRATEGIC ALLIANCE BETWEEN CHINESE AND MOZAMBICAN SMES ON FINANCIAL INCLUSION, INNOVATION, SUSTAINABILITY, MARKETING, THROUGH COLLABORATION - Manhique, Enoque Albino; PARRUQUE, CASTIGO JOSEEFA; YAQUN, Yi Yaqun; Macaneta, Aida Luis; Suzanne, xushan (ALBA - ISFIC Research and Science Journal, 2025)
Small and Medium Enterprises (SMEs) are greeted due to their crucial role in endorsing public financial development and reasonable maintainable development. They pay considerably value to the Gross Domestic Product (GDP), export payments earnings and employment generation in many nations and have been amply approved as the catalyst for sustainable economic development. The present research is about “A comparative study of Strategic Alliance between Chinese and Mozambican SMEs within the SMEs collaboration perspective with focus on SMEs development, financial Access, innovation, Regulations, sustainability, marketing access and firms’ performance. The study was conducted in Maputo, city and Maputo Province. A questionnaire survey was designed and applied to 32 SMEs managers. The respondents were selected randomly. The Questionnaire was distributed using different methods such direct personal contact and digital platforms (E-mail and WhatsApp). The data were processed and analysed using IBM-SPSS statistical Package version 20. The study fills a research gap by conducting a comparative analysis between Chinese and Mozambican SMEs with focus on the aspects previously mentioned. This study is very important for the whole country and for researchers and academician as it is unique with such nature in the country.